Intangible cultural heritage and public policies in Portugal – an overview - Carvalho, Ana (2022)
By signing the 2003 UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage (ICHC), states parties commit to implementing its guidelines in national contexts, adapting policies, procedures and heritage management systems to include the UNESCO principles and an understanding of Intangible Cultural Heritage (ICH), as well as considering community participation central to safeguarding processes. For many countries, this has resulted in framing new discourses, policies and practices that have contributed to a new reflection on how ICH is understood and how safeguarding is approached. Portugal is among the countries which, by ratifying the ICHC in 2008, set in motion a new heritage policy and governance framework for the safeguarding of ICH. This chapter presents an overview of the main steps taken in public polices concerning ICH, reflecting on the effects and challenges posed. This empirical study is based on the analysis of official documents (e.g., legislation and reports) and a literature review. The analysis presented herein may be significant to identify key issues in the implementation of ICHC in Portugal, and thus contribute to a comparative overview of the diverse approaches and effects generated by UNESCO.